The Effect of Turnover Intention on Employee Productivity of PT. Bangun Bersama Computindo Jakarta - Mulyana, Aida; Irawan, Pristanto Ria; Taryanto, Taryanto; Fa’uzobihi, Fa’uzobihi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aim of this research is to determine the effect of turnover intention on employee productivity PT. Bangun Bersama Computindo Jakarta. This research uses a quantitative descriptive method with data collection techniques through distributing questionnaires and library data. In this study, the sample used the Slovin formula 55 employees on variable turnover PT. Bangun Bersama Computindo Jakarta, using simple linear regression data analysis techniques. The results of this research show that there is no influence between turnover intention to employee productivity, and variable turnover intention has a correlation currently and has an influential contribution of 19,7% on employee productivity variables. It is hoped that the results of this research will contribute to further research.